2011
DOI: 10.1007/s10661-011-2134-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic mercury, cadmium, and lead in mink and otter from New York State: monitoring environmental contamination

Abstract: Many non-linear processes link atmospheric emissions to the bioavailability of metals; consequently, the monitoring of metals in ecosystem components is required to model their ecodynamics. American mink (Neovison vison) and river otter (Lontra canadensis) have the potential to serve as an upper-level-consumer component in monitoring metals bioavailability. However, the relationship of bioaccumulated metals to various environmental factors has not been explored nor have the effects of demographic factors been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 110 publications
(130 reference statements)
1
7
0
Order By: Relevance
“…However, such differences have been recorded in the case of mercury in some studies: concentrations of Hg were greater in female than male mink tissues (Gamberg et al 2005) or just in livers (Yates et al 2005). Mayack (2012) recorded higher concentrations of Hg and Cd in female mink and explained this finding by gender differences in relative growth. On the other hand, it was found that lead concentrations were higher in male mink (Mayack 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, such differences have been recorded in the case of mercury in some studies: concentrations of Hg were greater in female than male mink tissues (Gamberg et al 2005) or just in livers (Yates et al 2005). Mayack (2012) recorded higher concentrations of Hg and Cd in female mink and explained this finding by gender differences in relative growth. On the other hand, it was found that lead concentrations were higher in male mink (Mayack 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mayack (2012) recorded higher concentrations of Hg and Cd in female mink and explained this finding by gender differences in relative growth. On the other hand, it was found that lead concentrations were higher in male mink (Mayack 2012). The feeding habits of mink are also gender related (Birks and Dunstone 1985), and result mostly from the well pronounced sex-related size dimorphism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental exposure to pollutants such as heavy metals (HM) can impact structures and functions being relevant for ecosystem integrity and human health [1][2][3][4][5][6]. To avoid such impacts due to atmospheric HM deposition, the Protocol on Heavy Metals of the Convention on Long-Range Transboundary Air Pollution, adopted in 1998, targets three particularly harmful metals: cadmium (Cd), lead (Pb) and mercury (Hg).…”
Section: Introductionmentioning
confidence: 99%